Effects of extracting solvents on total phenolic content, total flavonoid content and anti-oxidant activity of Andrographis paniculata from Kemaman, Malaysia (Article) - Khamsah Suryati, Mohd; Saravanan, A Dharmaraj; U.S. Mahadeva, Rao (2015)
Andrographis paniculata Nee belonging to the family Acanthaceae, is common in Malaysia, Thailand and India. Traditionally, it has been used to treat many diseases including diabetes, upper respiratory tract infections and diarrhoea. The effect of extracting solvents (methanol, ethyl acetate, 50% ethanol/water and aqueous) on total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of whole Andrographis paniculata was studied. TPC was measured using Folin-Cioucalteu method while TFC was determined using aluminium chloride method. Antioxidant activity was determined using 2, 2-diphenyl-1picrylhydrazyl (DPPH) free radical scavenging assay. The aqueous extract recorded the highest phenolic content (184.48 mg GAE/g), followed by ethanol:water (1:1 v/v), methanol and ethyl acetate (178.79, 58.78, 9.37 mg GAE/g) respectively. One way ANOVA showed that the TPC of aqueous and ethanol:water extracts did not differ significantly at p˂0.05 among them but they differed from the other two extracts. Similarly, ethyl acetate extract recorded the highest TFC (0.44 mg QE/g) while methanol, ethanol:water and aqueous had similar average values for TFC at 0.43 mg QE/g. Consequently, the value for ethyl acetate extract was statistically different with the three others. Moreover, the antioxidant activity of ethanol:water indicated a good IC50 (93.30µg/ml) as compared to the standard (quercetin at 20 µg/ml) used in the experiment, while the other extracts have activity below 50%. The result of this study showed that TPC, TFC as well as antioxidant activity was influenced by extracting solvents and the choice of solvent for further study is suggested to be combination of ethanol:water. This is because it is similar statistically to aqueous in phenolic content and has highest antioxidant activity, which is beneficial for many diseases.